A Biomaterial‐Based Hedging Immune Strategy for Scarless Tendon Healing. Issue 19 (5th April 2022) - Wang, Zhen; Xiang, Lei; Lin, Feng; Tang, Yunkai; Deng, Lianfu; Cui, Wenguo
Abstract: Scarring rather than regeneration, is an inevitable outcome of unbalanced amplifications of inflammation‐destructive signals and atresia of the regenerative niche. However, identifying and effectively hedging against the risk of scarring and realizing the conversion of regenerative cues remain difficult. In this work, a hedging immune strategy based microfibrous membrane (Him‐MFM), by tethering distearoyl phosphoethanolamine layer‐supported copoly(lactic/glycolic acid) electrospun fibers with identified CD11b + /CD68 + scarring subpopulation membranes in the immune landscape after tendon injury to counterweigh tissue damage, is reported. Him‐MFM, carrying relevant risk receptors is shown to shift high type I biased polarization, alleviate apoptosis and metabolic stress, and mitigate inflammatory tenocyte response. Remarkably, the hedging immune strategy reverses the damaged tendon sheath barrier to the innate IL‐33 secretory phenotype by 4.36 times and initiates the mucous‐IL‐33‐Th2 axis, directly supplying a transient but obligate regenerative niche for sheath stem cell proliferation. In murine flexor tendon injury, the wrapping of Him‐MFM alleviates pathological responses, protects tenocytes in situ, and restores hierarchically arranged collagen fibers covered with basement membrane, and is structurally and functionally comparable to mature tendons, demonstrating that the hedging immunity is a promising strategy to yield regenerative responses not scarring. Abstract : Electrospun‐fiber‐tethered scarring subpopulation membranes are fabricated to shift type I biased polarization, alleviate stress, and mitigate inflammatory depression. Wrapping Him‐MFM alleviates pathological responses, protects tenocytes in situ, and restores hierarchically arranged collagen fibers covered by a basement membrane, structurally and functionally similar to mature tendons, demonstrating a promising strategy to yield regeneration.